2019
DOI: 10.1038/s41467-019-12793-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal insulin resistance multigenerationally impairs synaptic plasticity and memory via gametic mechanisms

Abstract: Metabolic diseases harm brain health and cognitive functions, but whether maternal metabolic unbalance may affect brain plasticity of next generations is still unclear. Here, we demonstrate that maternal high fat diet (HFD)-dependent insulin resistance multigenerationally impairs synaptic plasticity, learning and memory. HFD downregulates BDNF and insulin signaling in maternal tissues and epigenetically inhibits BDNF expression in both germline and hippocampus of progeny. Notably, exposure of the HFD offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 67 publications
2
56
1
Order By: Relevance
“…In addition, maternal obesity adversely affects BDNF/tropomyosin receptor kinase B (TRKB) signaling in the placenta in a sexually dimorphic manner [34]. Recently, Fusco et al showed maternal HFD-dependent insulin resistance downregulates BDNF and insulin signaling in maternal tissues and inhibits BDNF expression in both the germline and hippocampus of progeny [35]. The role of BDNF in developmental programming is highlighted by Briana et al [36].…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…In addition, maternal obesity adversely affects BDNF/tropomyosin receptor kinase B (TRKB) signaling in the placenta in a sexually dimorphic manner [34]. Recently, Fusco et al showed maternal HFD-dependent insulin resistance downregulates BDNF and insulin signaling in maternal tissues and inhibits BDNF expression in both the germline and hippocampus of progeny [35]. The role of BDNF in developmental programming is highlighted by Briana et al [36].…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…On the third day (test session), a new object replaced one of the old objects. Animals were allowed to explore for 10 min and a preference index, calculated as the ratio between time spent exploring the novel object and time spent exploring both objects, was used to measure recognition memory (Fusco et al, 2019).…”
Section: Memory Testmentioning
confidence: 99%
“…Progeny born to mothers who ate an HF diet also tend to eat an HF diet when growing and have been found to develop metabolic problems [27,28]. Thus, the generational transmission of obesity is cyclical [29].…”
Section: Introductionmentioning
confidence: 99%